The Power and Peril of Precise vs. Round Health Message Interventions to Increase Stair Use - Krull, Sebastian; Boecker, Lea; Loschelder, David D. (Frontiers in Psychology, 2021)
Taking the stairs versus an elevator generates benefits for the individual by increasing overall physical activity, health, and well-being. In the present paper, we report two pre-registered field intervention studies that examine how health message interventions can motivate individuals to change their behavior. We empirically contrasted opposing predictions from the literature as to whether numerically round (60.00%) or precise (61.87%) health messages are more effective in causing people to use the stairs over taking the elevator. Both interventions were compared to a control condition (no-health message). Contrary to our hypotheses and extant findings, both intervention studies did not produce a significant positive effect of the interventions relative to the control condition. In psychology’s ongoing ‘renaissance’ (Nelson et al., 2018), such null findings have received increasingly more appreciation, particularly in the light of evident downsides of file-drawered studies (Friese & Frankenbach, 2019). We discuss a number of moderating factors that may determine when and why nudging interventions are (in-)effective (e.g., a-priori behavioral prevalence, preestablished habits, ceiling effects, building infrastructure), as well as limitations and avenues for future research.